PENGARUH LATIHAN ZUMBA TERHADAP Nilai FEV1 (Forced Expiratory Volume in one second) - Jayanti, Yusnia (Universitas Sam Ratulangi, 2014)
Abstract: The modern technology brings negative impact to human life that is the lack of physical activity which is not good for health and can cause varieties of diseases. Some studies show that lack of physical activity can lower pulmonary resistance and also a major cause of morbidity and mortality. Zumba is a Latine-inspired danse workout first developed in Columbia. The improvement of respiratory muscle endurance is gained from physical exercise . One asessment is a measurement of lung function FEV1 ( Forced expiratory volume in one Second ) which can provide information on the maximum rate of air flow in the lung. This study have a purpose to find out the influence of zumba exercise against FEV1 value of female students year 2013 Medical Faculty of Nursing Science Sam Ratulangi University hwo with less of physical or sport activities and meet the inclusion criteria. This was an experimental study with one group pre and post test design. Data was analyzed by paired t test using SPSS. The results showed significant differences between the average values of FEV 1 before and after 2 weeks of zumba exercise with P = 0,044 (P < 0.05). Conclusion: There was an increase of FEV 1 value after 2 weeks of Zumba exercise.Keywords: physical exercise, FEV1, Zumba.Abstrak: Kemajuan teknologi moderen membawa dampak negatif bagi masyarakat yaitu Kurangnya aktifitas fisik yang dapat berdampak buruk bagi kesehatan yaitu timbulnya berbagai penyakit. Beberapa penelitian menunjukkan berkurangnya aktifitas fisik dapat menurunkan daya tahan paru serta merupakan penyebab utama morbiditas dan mortalitas. Zumba merupakan latihan tari Latin yang terinspirasi pertama kali dan dikembangkan di Columbia. Peningkatan daya tahan otot pernapasan dapat diperoleh dari latihan fisik. Salah satu penilaian fungsi paru adalah pengukuran FEV1 (Forced Expiratory Volume in one Second) yang dapat memberikan informasi tentang laju aliran udara maksimal dalam paru. Penelitini ini ber tujuan untuk mengetahui pengaruh latihan zumba terhadap nilai FEV1 pada Mahasiswi Program Studi Ilmu Keperawatan angkatan 2013 Universitas Sam Ratulangi yang kurang melakukan aktivitas fisik atau olahraga dan memenuhi kriteria. Metode penelitian ini bersifat eksperimental dengan rancangan one group pre and post test design. Data dianalisis dengan uji t berpasangan menggunakan SPSS. Hasil penelitian ini menunjukkan perbedaan signifikansi antara nilai rata-rata FEV1 sebelum dan setelah 2 minggu latihan zumba P = 0,04 (P < 0,05). Simpulan: Terdapat peningkatan nilai FEV1 sesudah 2 minggu latihan zumba.Kata kunci : aktifitas fisik, FEV1, Zumba.